EFEKTIFITAS PENERAPAN TERHADAP TINDAK PIDANA TAMBAHAN UANG PENGGANTI DALAM TINDAK PIDANA KORUPSI - Haryadi, Tobi; Riviyusnita, Rianda; Zakaria, Zakaria (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2023)
Eradicating criminal acts of corruption is part of a criminal justice system that relies solely on repressive channels, because simply by bringing corruptors to court it is impossible to suppress the rate of development of criminal acts of corruption. The magnitude of state financial losses caused by corruption is very disproportionate to the magnitude of returns to state finances due to corruption. The implementation of returning state financial losses resulting from criminal acts of corruption cannot just be done immediately. Apart from waiting for the payment of replacement money from those convicted in corruption cases which takes a long time, the return of replacement money to the state treasury cannot be done immediately. This is due to the need to go through bureaucratic procedures. By using a normative juridical research methodology the author intends to find answers to existing problems. The effectiveness of the application of additional criminal compensation money in order to recover state financial losses in criminal acts of corruption is not yet effective, in this case the convict's assets have already been confiscated. This proves that it takes a very long time to obtain restitution for state financial losses with replacement money from the convicts. The implementation of restitution of State financial losses requires payment of compensation money directly or if the defendant does not pay the replacement money within 1 month after the court decision has permanent legal force, then his property can be confiscated and then auctioned to cover the replacement money.